Initial experience with robotic-assisted thoracic surgery for superior mediastinal masses - Yang, Bo; Chen, Ruiji; Li, Chengrun; Fan, Kaijie; Lin, Yingxue; Liu, Yang (Frontiers in Surgery, 2023)
Objective: Minimally invasive surgery is challenging for masses located in the superior mediastinum, especially for those close to the chest outlet. This study aimed to evaluate the feasibility and safety of robotic-assisted thoracic surgery (RATS) for these masses. Methods: From June 2015 to January 2020, 35 patients (19 males, 16 females), with a mean age of 41.6 (range, 13–66) years, underwent RATS for the treatment of superior mediastinal masses. Data regarding the operation time, blood loss, pathology, conversion rate, morbidity, mortality, and cost were collected and analyzed. Results: The mean (±standard deviation) operation time, blood loss, chest tube use duration, and postoperative hospital day were 117 ± 45.2 (range, 60–270) min, 59.7 ± 94.4 (range, 10–500) mL, 4.1 ± 2.1 (range, 1–10) days, and 5.1 ± 2.1 (range, 2–11) days, respectively. The pathological diagnoses included schwannoma (26 cases), ganglioneuroma (4 cases), bronchogenic cysts (3 cases), ectopic nodular goiter (1 case), and cavernous hemangioma (1 case). The mean diameter of the resected tumor was 4.6 ± 2.0 (range, 2.5–10) cm. No conversion or mortality occurred. Postoperative complications included Horner’s syndrome (18 cases: 6 patients with preoperative Horner’s syndrome), weakened muscular power (2 cases), and chylothorax (2 cases). The mean cost was $ 8,868.7 (range, $ 4,951–15,883). Conclusions: Our experience demonstrated that RATS is safe and feasible for superior mediastinal mass resection. However, the high incidence of postoperative Horner’s syndrome requires further research.